Integrasi Sosiokultural Siswa Dalam Pendidikan Multikultural Melalui Pembelajaran Sejarah - Yusuf Perdana; Sumargono Sumargono; Valensy Rachmedita (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2019)
this research aims to cultivate the values ​​of multiculturalism in historical learning through the integration of students' social-cultural conditions, describing students' understanding of the students' social-cultural conditions and the implementation of multiculturalism values ​​by students in their daily lives. This research is qualitative with a phenomenological approach, namely by conducting a critical analysis of social phenomena. The technique of data collection is done by observation, interview, and documentation. The validity of data analysis techniques uses triangulation techniques and sources. The data analysis used is an interactive analysis model. Based on the results of the study, it was explained that in the SMAN 3 Surakarta the history teacher had integrated sociocultural students in multicultural education through historical learning. Historical teachers and students feel the benefits of historical learning through multicultural education by remembering and studying the riots triggered by differences to other historical events backed by ethnic conflicts such as Riots in Surakarta to the opposite of the Youth Oath which was pioneered by various ethnic, ethnic and religion throughout Indonesia.